Electric Field-Modulated Surface Enhanced Raman Spectroscopy by PVDF/Ag Hybrid - Lu, Jiajun; Song, Yuzhi; Lei, Fengcai; Du, Xuejian; Huo, Yanyan; Xu, Shicai; Li, Chonghui; Ning, Tingyin; Yu, Jing; Zhang, Chao (Scientific reports, 2020)
Electrically modulated surface enhanced Raman scattering (E-SERS) can be able to regulate the plasmon resonance peak of metal nanostructures, further improve the detection sensitivity of the SERS substrate. However, the E-SERS substrates require auxiliary equipment to provide the electrical potential, and most of them are non-flexible structure, which limits the application of E-SERS in the portable, in-situ and fast detection area. Here, we developed an electric field-modulated SERS substrate based on the piezoelectric effect by combining the PVDF (piezoelectric-modulated layer) and Ag nanowires (AgNWs) (SERS active layer) and investigated the SERS activity in experiment and theory. The enhanced electric field and the tunable plasmon resonance induced by the piezoelectric effect provide the additional enhancement for the SERS signal. Furthermore, we fabricated a SERS active ring with a piezoelectric field-modulated substrate and achieved the in-situ detection of glucose with a non-invasive method. This work provided innovation for the E-SERS and could greatly promote the development of the in-situ , wearable and intelligent sensors.